Experimental Investigation of Tensile and Impact Behavior of Aramid-Natural Fiber Composite. (2019) - Rajesh, S.; Vijayaramnath, B.; Elanchezhian, C.; Vivek, S.; Prasadh, M. Hari; Kesavan, M.
Abstract: For past few decades there is tremendous growth in science and technology which demands new materials. To meet such demands for materials, the world's focus is towards emerging and promising field of Composite materials, the reason being is that composite materials are light weight and high strength to weight ratio when compared to most conventional metals. The main purpose of this paper is to investigate tensile and impact property of Aramid with natural fiber composite. Kevlar being the main reinforcement along with Neem/Kenaf and matrix is Epoxy resin. The main reason of choosing Kevlar as main reinforcement as it has good strength, high impact and high energy absorption capacity but Kevlar being quiet costlier so Kenaf and Neem is used alternatively to reduce the cost and to replace and substitute the Kevlar with natural fibers without affecting the impact resistance property. Mechanical properties such as tensile, impact are found and the results are plotted.